Characteristics of the macroinvertebrate community structure and their habitat suitability conditions in the Chishui River - Li, Xinyu; Yan, Long; Zhi, Xu; Hu, Peng; Shang, Chongju; Zhao, Baolong (Frontiers in Ecology and Evolution, 2025)
IntroductionAs an important tributary of the upper Yangtze River without dams, the study of the macroinvertebrate community structure and habitat suitability conditions in the Chishui River holds significant implications for water ecological conservation and restoration.MethodsIn order to explore the species composition, community characteristics and their ecological needs of macroinvertebrates in the Chishui River, 26 sampling sites were deployed in the Chishui River in this study in March (dry season), July (wet season), and November (normal season) of 2023 and performed community structure analysis.ResultsA total of 153 macroinvertebrate taxa were identified, with 62 taxa recorded in the dry season, 46 in the wet season and 115 in the normal season. The assemblage was predominantly composed of aquatic insects from the EPT group (Ephemeroptera, Plecoptera and Trichoptera). The results of ANOSIM analysis indicate that the species composition of macroinvertebrates varies significantly across different water periods. The Shannon-Wiener diversity index and Margalef index were significantly higher during the normal season compared to the dry and wet seasons. In contrast, the Pielou index and Simpson index remained relatively stable, suggesting a higher level of evenness in community structure across the different water periods. Based on the habitat suitability curves, Corbicula fluminea and Heptagenia prefer environments with high flow velocities and substrate particle sizes (D50) smaller than 300 mm. Hydropsyche sp.1 and Baetis thrive in environments with medium to low water depths, high flow velocities, and D50 ranging from 100 to 300 mm. Caridina favor deeper waters, low flow velocities, and larger substrate particles. The GAM fitting results revealed that the number of macroinvertebrate taxa increased with rising pondus hydrogenii (pH) and electrical conductivity (EC) levels. Species richness initially declined and then rose within certain thresholds of total nitrogen (TN) and total phosphorus (TP) concentrations. The optimal conditions for macroinvertebrate communities in the Chishui River were determined to be a DO concentration of 9.8 mg/L and an NH3-N concentration of 0.12 mg/L.DiscussionOverall, the macroinvertebrate community structure in the Chishui River is significantly influenced by factors such as water quality, flow velocity, and substrate particle size, and it demonstrates strong adaptability to seasonal variations.